2021
DOI: 10.1016/j.talanta.2021.122207
|View full text |Cite
|
Sign up to set email alerts
|

Anti-SARS-CoV-2 IgG and IgM detection with a GMR based LFIA system

Abstract: Since December 2019, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has caused millions of deaths and seriously threatened the safety of human life; indeed, this situation is worsening and many people are infected with the new coronavirus every day. Therefore, it is very important to understand patients’ degree of infection and infection history through antibody testing. Such information is useful also for the government and hospitals to formulate reasonable prevention policies and treatment plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 20 publications
(13 reference statements)
0
49
0
Order By: Relevance
“…The sensitivity, specificity, positive predictive value, and negative predictive value of the kit were calculated according to the following formulas [21] : \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}\begin{align*} \text {Sensitivity}=&\Biggl[\text {True Positive}/\Biggl(\text{True Positive} \\&+\, \text {False Negative}\Biggr)\Biggr] \times 100{\%}\\ \text {Specificity}=&\Biggl[\text {True negative} / \Biggl(\text {True Negative} \\&+\, \text {False Positive}\Biggr)\Biggr] \times 100{\%}\\ \text {Positive predictive value}=&\Biggl[\text {True Positive} / \Biggl(\text {True Positive} \\&+\, \text {False Positive}\Biggr)\Biggr] \times 100{\%}\\ \text {Negative predictive value}=&\Biggl[\text {True Negative} / \Biggl(\text {False Negative} \\&+\, \text {True Negative}\Biggr)] \times 100{\%}\end{align*} \end{document} …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity, specificity, positive predictive value, and negative predictive value of the kit were calculated according to the following formulas [21] : \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}\begin{align*} \text {Sensitivity}=&\Biggl[\text {True Positive}/\Biggl(\text{True Positive} \\&+\, \text {False Negative}\Biggr)\Biggr] \times 100{\%}\\ \text {Specificity}=&\Biggl[\text {True negative} / \Biggl(\text {True Negative} \\&+\, \text {False Positive}\Biggr)\Biggr] \times 100{\%}\\ \text {Positive predictive value}=&\Biggl[\text {True Positive} / \Biggl(\text {True Positive} \\&+\, \text {False Positive}\Biggr)\Biggr] \times 100{\%}\\ \text {Negative predictive value}=&\Biggl[\text {True Negative} / \Biggl(\text {False Negative} \\&+\, \text {True Negative}\Biggr)] \times 100{\%}\end{align*} \end{document} …”
Section: Methodsmentioning
confidence: 99%
“…We confirm that the detection results of COVID-19 patients in this study have not been reported in any other submission by us or anyone else. The sensitivity, specificity, positive predictive value, and negative predictive value of the kit were calculated according to the following formulas [21]…”
Section: F Clinical Sample Validationmentioning
confidence: 99%
“…Inspired by this pioneering work, increasing efforts have been devoted to improve the multiple sensing capability of LFIA for the sensitive and simultaneous detection of SARS-CoV-2-specific IgM and IgG [ 112 , 113 ]. Among these studies, except for the common AuNPs [ 114 , 115 ], other nanomaterials including selenium nanoparticle, quantum dots (QDs) [ 116 ] or QD nanobeads [ 117 ], lanthanide fluorescent microsphere [ 118 ], aggregation-induced emission based polymeric nanoparticles [ 119 ], core–shell SiO 2 @AgNPs [ 120 ], and magnetic nanoparticles [ 121 ], have also been used in LFIA for enhancing the detection of SARS-CoV-2 antibodies with the help of sensitive signal outputs of colorimetry, fluorescence, surface enhanced Raman scattering, and giant magnetoresistance. In addition, the serologic test performance of these reported multiple LFIA for COVID-19 can be further improved by integrating with a machine-learning classifier to control the false positive rate at a targeted level [ 122 ].…”
Section: Lfa For Antibody Testmentioning
confidence: 99%
“…At present, great advancements have been made to achieve the diagnosis of SARS-CoV-2, including reverse transcription-polymerase chain reaction (RT-PCR) and the antibody detection method [6][7][8][9][10][11]. Based on the known RNA sequence of the virus, the RT-PCR technique can be used to convert the viral RNA in the nasal or the throat into DNA, and the DNA concentration will be subsequently amplified and detectable.…”
Section: Introductionmentioning
confidence: 99%